NOD1: a metabolic modulator - Tang, Ruobing; Xie, Chunguang; Zhang, Xiyu (Frontiers in Endocrinology, 2025)
Nucleotide-binding oligomerization domain 1 (NOD1) is an intracellular pattern recognition receptor that detects injury signals and initiates inflammatory responses and host defense. Furthermore, NOD1 serves as a metabolic mediator by influencing the metabolism of various tissues, including adipose tissue, liver, cardiovascular tissue, pancreatic β cells, adrenal glands, and bones through diverse mechanisms. It has been discovered that activated NOD1 is associated with the pathological mechanisms of certain metabolic diseases. This review presents a comprehensive summary of the impact of NOD1 on tissue-specific metabolism.